2018
DOI: 10.1074/jbc.ra118.003628
|View full text |Cite
|
Sign up to set email alerts
|

Delineating FtsQ-mediated regulation of cell division in Mycobacterium tuberculosis

Abstract: Identifying and characterizing the individual contributors to bacterial cellular elongation and division will improve our understanding of their impact on cell growth and division. Here, we delineated the role of , a terminal gene of the highly conserved division cell wall () operon, in growth, survival, and cell length maintenance in the human pathogen (). We found that FtsQ overexpression significantly increases the cell length and number of multiseptate cells. FtsQ depletion in resulted in cells that were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 89 publications
2
34
0
Order By: Relevance
“…However, despite the differences in reports of essentiality, the rest of our studies report similar phenotypes to the conditional mutants characterized in these previous studies, particularly the elongated cells and altered septation patterns. Thus, this work, along with the previous findings of Wu et al [14] and Jain et al [15], does identify a key role for sepIVA in septation and warrants further studies to decipher its precise role.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…However, despite the differences in reports of essentiality, the rest of our studies report similar phenotypes to the conditional mutants characterized in these previous studies, particularly the elongated cells and altered septation patterns. Thus, this work, along with the previous findings of Wu et al [14] and Jain et al [15], does identify a key role for sepIVA in septation and warrants further studies to decipher its precise role.…”
Section: Discussionsupporting
confidence: 67%
“…It is unlikely that downstream effects on MSMEG_2417 might have led to a different outcome of essentiality in these two studies, as MSMEG_2417 is not essential in M. smegmatis [26]. Moreover, the conditional mutants described in these studies showed similar phenotypes to WT M. smegmatis under conditions that allowed for expression of SepIVA function [14,15]. Rv2927c is predicted to be essential in M. tuberculosis, but M. smegmatis can tolerate the loss of genes known to be essential in M. tuberculosis.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In other organisms, loss of any of these fts genes blocks division completely, leading to long filamentous cells or loss of viability (21). However, decreased levels of these genes cause more moderate phenotypes, in particular, depletion of either ftsA or ftsQ leads to increased cell length in other bacteria (40,41), similar to the longer length observed in ΔntrYX cells that have twofold lower levels of ftsA and ftsQ transcripts ( Table 1). Thus, it is likely that direct regulation of cell division genes in the dcw cluster contributes to the slowed initiation and progression of cell division, decreased grown rate, and altered cell shape of the NtrYX mutant.…”
Section: Discussionmentioning
confidence: 76%